Simplify: -27x^3yz over 36x^2y^2z

-27x^3yz/36x^2y^2z = [(9x^2yz)(-3x)]/[(9x^2yz)(4y)] = -3x/4y

Question

Asked 12/18/2010 7:52:31 PM

Updated 6/22/2014 2:26:53 AM

1 Answer/Comment

Rating

3

-27x^3yz/36x^2y^2z

= [(9x^2yz)(-3x)]/[(9x^2yz)(4y)]

= -3x/4y

= [(9x^2yz)(-3x)]/[(9x^2yz)(4y)]

= -3x/4y

Added 6/22/2014 2:26:53 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [6/22/2014 2:41:04 AM]

Working with polynomial: (5x – 3.6) – (4x + 1.2)

Question

Expert Answered

Updated 7/3/2014 1:57:21 PM

1 Answer/Comment

Working with polynomial: (3x^2 + 3x) + (4x + 4). Please show the steps on how you got your answer. Thanks!

Question

Updated 8/10/2014 5:55:48 PM

1 Answer/Comment

(3x^2 + 3x) + (4x + 4)

= 3x^2 + 3x + 4x + 4;

= 3x^2 + 7x + 4

= 3x^2 + 3x + 4x + 4;

= 3x^2 + 7x + 4

Added 8/10/2014 5:55:48 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [8/10/2014 5:57:18 PM]

Given the polynomial x^7 + 3x^2 - 4x^8 + 7x^3, what is the degree of the polynomial? **Weegy:**
x^7 + 3x^2 - 4x^8 + 7x^3, the degree of the polynomial is 8.
ser: Solve for x: -4x + 7 = 35 **Weegy:**
4x + 7 = 35;
4x = 35 - 7;
4x = 28;
x = 28/4;
x = 7
**User:** Solve for x: -2(x-4) = -3(x + 8) **Weegy:**
-2(x - 4) = -3(x + 8);
-2x + 8 = -3x - 24;
-2x + 3x = -24 - 8;
x = -32
(More)

Question

Expert Answered

Updated 12/26/2014 7:53:18 AM

0 Answers/Comments

30,149,066

questions answered

There are no comments.